Предмет: Алгебра,
автор: MrsVaderr
Решите уравнение:
Ответы
Автор ответа:
5
................,.............
Приложения:
666uukk:
вы решили через дискриминант?
легче было сделать замену y=x+4
(y+1)^4 + (y-1)^4 = 2
y^4+4y^3+6y^2+4y+1+y^2-4y^3+6y^2-4y+1=2
2y^4 + 12y^2 = 0
2y^2(y^2+6)=0
y=0
x=-4
все решение
один из вариантов решение - на будущее
Похожие вопросы
Предмет: Алгебра,
автор: Аноним
Предмет: Информатика,
автор: Danilchik06
Предмет: Математика,
автор: sonj020910
Предмет: Химия,
автор: nyuskokoptyako
Предмет: Литература,
автор: natashasera